KH. ABU BAKAR BASTARI PERAN TERHADAP PERKEMBANGAN ISLAM DI PALEMBANG (1925-1971) - Muhammad Soleh (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2020)
Ulama was one of the important figures in the spread and development of Islam in a region. This study aimed to reveal the active role of a major scholar in the development of Islam in Palembang in the middle of the 20th century named K.H. Abubakar Bastari. The research method used to facilitate the implementation or research activities in order to achieve predetermined goals, namely historical method, with stages: heuruistics, criticism, interpretation, and historiography. The resultof the study revealed that as a scholar who played a role in the spread of Islam in Palembang. K.H. Abubakar Bastari also did not ignore the world of Islamic education. K.H.'s concern Abubakar Bastari in Islamic education in the Palembang region, he found the Tsanawiyah level Nurul Falah madrasah in 1926 and he was also the pioneer of the establishment of the Islamic College of South Sumatra which is known as Raden Fatah State Islamic University in Palembang and have roles in various fields such as politics, economics, culture and religion in South Sumatra.